(3GdUMGaI GdGdcJQhfjI h GdJWHjbGJ GdGYdGejI GdMOjKI (B/s - (3HYRjR, EHQGgje s ((3GdbGgQI (B:s (3OGQ GdcJGH GdMOjK ,s, 2020)
(3dGHO ef JMdjd h eYGdLI GdUMGaI GdGdcJQhfjI HeaghegG GdhGSY h OQGSI cd GdbVGjG h GdLhGfH GdGLJeGYjI GdeJYdbI HgG h dPdc fMf df fZhU aj GdLhGfH GdJbfjI ddUMGaI GdGdcJQhfjI HbOQ eG fZhU aj LhGfHgG GdfXQjI h efGgLgG h GfeGWgG h JGKjQgG h aj cGaI GdXhGgQ GdGLJeGYjI h GdGYdGejI h GdKbGajI GdJj GKQJ ajgG Gh JGKQJ HgGs
Keywords: (3GdUMGaI GdEdcJQhfjIs; (3hSGFd GdEYdGe s